The criminal Google generation: The Camorra youth on Facebook (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
The present essay, after an introduction that reconstructs - through the news appearing in the media - the various stages of virtual rooting of the Camorra, focuses on the criminal Google generation. It is proposed, a research that applies the "historical gaze" (Gruzinski, 2016) to the use of Facebook by the boys affiliated to the Camorra clans. The author, in fact, presents a research that applies the "historical gaze" (Gruzinski, 2016) to the use of Facebook by the boys affiliated to the Camorra clans. From the survey of individual profiles, emerges the formation of a criminal "interreal" dimension. The practices of impression management and personal brand competing on the one hand to pass on the traditional mafia imaginary through online sharing of media content (now globalized), on the other hand to innovate the slang language through the use of images and iconic signs such as the emoji.Keywords: Camorra, Facebook, Google Generation, Imaginary, Interreal